Material for curing metal ions in coal gangue as well as preparation method and application of material
By using polyacrylamide and other materials in coal gangue to react with alkali liquid to form a gel, the problem of metal ions escape in coal gangue is solved, and the effective curing and long-term sealing of metal ions are achieved.
Patent Information
- Application Number
- CN202411778239.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
The existing technology is difficult to apply on a large scale to solidify metal ions in coal gangue, and it is impossible to effectively solve the problem of metal ions escape in coal gangue.
A material including polyacrylamide, fly ash, crosslinking agent, calcium oxide, chitosan, montmorillonite, magnesium fibres and rubber particles is used to form a gel in situ between the coal gangue through the action of alkali liquid, sealing the pore structure of the coal gangue and preventing the escape of metal ions.
Effectively cure metal ions in coal gangue, reduce the escape and mobility of metal ions, and achieve the effect of long-term curing.
Smart Images

Figure BDA0005172077010000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of treatment of metal ions in coal gangue for solidification, and in particular to a material for solidifying metal ions in coal gangue, and a preparation method and application thereof. Background Art
[0002] Gangue is a solid waste generated during coal mining and washing. If gangue is abandoned and piled in the open air, it will form a gangue mountain. The escape or leaching of harmful substances in it will pollute the atmosphere, farmland and water bodies, causing environmental pollution. It can also enter the human body through environmental media and threaten human health. The resource utilization of gangue is of great significance to environmental protection and resource conservation. In many studies, the solidification of metal ions in gangue is a key issue because it is related to the high added value utilization and environmental safety of gangue.
[0003] Coal gangue contains a variety of metal ions, including valuable metals such as aluminum, iron, lithium, and rare earths, as well as toxic heavy metals such as chromium and mercury. Researchers have developed a variety of methods to solidify metal ions in coal gangue. A special ion curing agent (ICG) is used to solidify coal gangue. This curing agent replaces weak cations on the surface and between layers of coal gangue with strong cations through cation exchange, thereby reducing the negative charge on the surface, reducing the hydrophilicity of the material, and reducing the content of surface bound water. This process not only changes the pore structure characteristics of coal gangue, but also improves its mechanical properties.
[0004] Gangue-loaded Fe / FeOx nanoparticles have also been studied for the adsorption of heavy metal ions Cd(II) in water. The nanoparticles prepared by chemical liquid phase reduction are formed on the surface of gangue, and the gangue is purified through a series of processes to achieve effective removal of Cd(II).
[0005] However, the above method has special requirements for the use scenario and cannot be applied on a large scale to solidify metal ions in coal gangue. Therefore, it is necessary to provide a better material for solidifying metal ions in coal gangue. Summary of the invention
[0006] In view of the limitations of the above-mentioned prior art, the present invention provides a material for solidifying metal ions in coal gangue, a preparation method thereof and an application thereof. The material for solidifying metal ions in coal gangue of the present invention uses multiple mechanisms to solidify and adsorb metal ions in coal gangue, and the material of the present invention can form a gel in situ between coal gangue, so that the gel is filled between the coal gangue, and an effective blockage is formed between the coal gangue, thereby preventing the escape of metal ions in the coal gangue caused by the scouring of liquids such as water, and effectively solving the problem of solidifying metal ions in coal gangue.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] The first aspect of the present invention is to provide a material for solidifying metal ions in coal gangue, characterized in that the material comprises the following raw materials in parts by weight: 15-40 parts of polyacrylamide, 10-30 parts of fly ash, 5-15 parts of a cross-linking agent, 10-25 parts of calcium oxide, 1-10 parts of chitosan, 1-10 parts of montmorillonite, 4-15 parts of brucite fiber, and 1-5 parts of rubber particles.
[0009] As a preferred embodiment of the above material, the material also includes 200-400 parts of alkali solution used therewith.
[0010] As a preferred embodiment, the material for solidifying metal ions in coal gangue includes the following raw materials in parts by weight: 20-30 parts of polyacrylamide, 10-20 parts of fly ash, 5-10 parts of cross-linking agent, 10-20 parts of calcium oxide, 2-6 parts of chitosan, 5-10 parts of montmorillonite, 5-8 parts of brucite fiber, and 1-3 parts of rubber particles.
[0011] As a further preferred embodiment of the above preferred embodiment, the material also includes 200-300 parts of alkali solution used therewith.
[0012] As a preferred embodiment, the cross-linking agent includes one or more of N,N'-methylenebisacrylamide, phenolic resin, hexamethylenetetramine, and formaldehyde.
[0013] As a preferred embodiment, the number average molecular weight of polyacrylamide is 3 million to 6 million.
[0014] As a preferred embodiment, the particle size of the fly ash is 120-150 mesh.
[0015] As a preferred embodiment, the particle size of calcium oxide is 100-150 mesh.
[0016] As a preferred embodiment, the number average molecular weight of the chitosan is 300,000-500,000.
[0017] As a preferred embodiment, the particle size of the montmorillonite is 10-20 mesh.
[0018] As a preferred embodiment, the length of the brucite fiber is 3-6 mm.
[0019] As a preferred embodiment, the rubber particles are selected from nitrile rubber particles, and preferably the particle size of the nitrile rubber particles is 80-120 meshes.
[0020] As a preferred embodiment, the alkali in the alkali solution is selected from sodium hydroxide and potassium hydroxide;
[0021] As a further preference, the weight proportion of the alkali in the alkali solution is 5-10 parts.
[0022] The second aspect of the present invention is to provide a method for preparing the material for solidifying metal ions in coal gangue as described in the first aspect of the present invention, comprising the following steps: (1) mixing the raw materials uniformly to obtain a mixture (hereinafter referred to as mixture A).
[0023] As a preference, the method further comprises storing separately the alkali solution and mixture A used in combination with the material.
[0024] The third aspect of the present invention is to provide an application of the material for solidifying metal ions in coal gangue as described in the first aspect of the present invention:
[0025] The material is mixed evenly with coal gangue to obtain a mixture B; the mixture B is spread into a 30-40 cm thick spreading layer; the alkali solution used in combination is heated and added to the mixture B for reaction to achieve in-situ gelation. Through the above application, the metal ions in the coal gangue are solidified, and a coal gangue solidified layer is obtained.
[0026] As a preferred implementation, the mass ratio of polyacrylamide to coal gangue in the material is 1:4-8.
[0027] As a preferred embodiment, the heating temperature of the alkali solution is 30-80°C.
[0028] As a preferred embodiment, the alkali solution is added to the mixture B in n times, and the amount of alkali solution each time is 1 / n of the volume of the alkali solution. The first alkali solution is added at a position 1 / n away from the bottom layer of the spreading layer of the mixture B, and the second alkali solution is added at a position 2 / n away from the bottom layer of the spreading layer of the mixture B. The above rule is repeated until the alkali solution is added. The value range of n is 3-4.
[0029] As a preferred embodiment, the temperature of the first addition of alkali solution is 60-80°C, preferably 70-80°C; the temperature of the first addition of alkali solution is denoted as T 1 The temperature of the nth addition of alkali solution is T 1 -10(n-1).
[0030] As a preferred embodiment, the time interval for adding the alkali solution each time is 15-30 minutes.
[0031] Principle of the invention:
[0032] When the material of the present invention is used to solidify metal ions in coal gangue, the following reactions are involved: fly ash, calcium oxide, coal gangue and a small amount of brucite fiber undergo polymerization reaction under the action of alkali solution, and the generated gel can effectively solidify the heavy metal ions in the coal gangue; in addition, a large amount of heat will be released during the polymerization reaction, and at the high temperature of heat release, polyacrylamide and cross-linking agent will also be gelled in situ and filled between the coal gangue to form a dense network structure, which will coat and seal the coal gangue, reduce the escape of metal ions in the coal gangue and the mobility of metal ions, and achieve a long-term solidification effect.
[0033] In the above technical solution of the present invention, chitosan and montmorillonite can effectively adsorb heavy metals; montmorillonite can also absorb water and swell, and the effectiveness of plugging is increased through the expansion filling and the compaction effect generated by the expansion; the rubber particles can be elastically deformed, and further fill the space between the coal gangue through deformation; the brucite fibers are distributed in both the gel of the geopolymerization reaction and the gel of the polyacrylamide polymerization, which can increase the bonding effect of the above two gels and increase the tightness of the contact of the above gels.
[0034] The gel system of the present invention is slightly alkaline. Under alkaline conditions, heavy metal ions are easily precipitated in the form of precipitation and are then easily adsorbed and wrapped by the gel, which is also beneficial to reducing the leaching of heavy metal ions.
[0035] The present invention has the following advantages:
[0036] The material for solidifying metal ions in coal gangue of the present invention utilizes multiple mechanisms to solidify and adsorb metal ions in coal gangue, and the material of the present invention can form gel in situ between coal gangue, so that the gel is filled between coal gangue, and an effective blockage is formed between coal gangue, thereby preventing the escape of metal ions in coal gangue caused by the scouring of liquids such as water, and effectively solving the problem of solidifying metal ions in coal gangue.
[0037] The material of the present invention has a simple application scenario when solidifying metal ions in coal gangue: the coal gangue and the material are spread into a layer, and then alkali solution is injected into the layer, so that the metal ions in the coal gangue can be effectively solidified, which can meet various scenario requirements when utilizing coal gangue resources. DETAILED DESCRIPTION
[0038] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0039] Example 1
[0040] A material for solidifying metal ions in coal gangue, comprising the following raw materials in parts by weight:
[0041] 15 parts of polyacrylamide, 30 parts of fly ash, 5 parts of cross-linking agent, 10 parts of calcium oxide, 6 parts of chitosan, 1 part of montmorillonite, 8 parts of brucite fiber and 4 parts of rubber particles.
[0042] Among them, the cross-linking agent is hexamethylenetetramine; the number average molecular weight of polyacrylamide is 5 million; the particle size of fly ash is 140 mesh; the particle size of calcium oxide is 120 mesh; the number average molecular weight of chitosan is 400,000; the particle size of montmorillonite is 20 mesh; the length of brucite fiber is 6 mm; the rubber particles are selected from nitrile rubber particles, and the particle size of nitrile rubber particles is 100 mesh; the alkali in the alkali solution is selected from sodium hydroxide; and the weight proportion of the alkali in the alkali solution is 7 parts.
[0043] When preparing the material for solidifying metal ions in coal gangue, the raw materials are mixed evenly to obtain a mixture A; 300 parts of alkali solution and the mixture A are stored separately.
[0044] When the above material is used to solidify metal ions in coal gangue, the mixture A in the material is evenly mixed with the coal gangue (the mass ratio of polyacrylamide to coal gangue is 1:5) to obtain a mixture B; the mixture B is spread into a 40 cm thick spreading layer; the heated alkali solution is added to the mixture B for reaction, wherein the alkali solution is added to the mixture B in 4 times, and the amount of alkali solution each time is 1 / 4 of the volume of the alkali solution, the first alkali solution is added at a position 1 / 4 of the bottom layer of the spreading layer of the mixture B, and the second alkali solution is added at a position 2 / 4 of the bottom layer of the spreading layer of the mixture B, and the above rule is repeated until the alkali solution is added; the temperature of the first alkali solution addition is 70°C; the temperature of the alkali solution addition for the 2nd to 4th time is 60, 50, and 40°C; the time interval between each addition of the alkali solution is 25 minutes; after the above reaction, in-situ gelation is achieved, thereby solidifying the metal ions in the coal gangue and obtaining a coal gangue solidification layer.
[0045] Example 2
[0046] A material for solidifying metal ions in coal gangue, comprising the following raw materials in parts by weight:
[0047] 30 parts of polyacrylamide, 10 parts of fly ash, 10 parts of cross-linking agent, 20 parts of calcium oxide, 2 parts of chitosan, 10 parts of montmorillonite, 8 parts of brucite fiber and 2 parts of rubber particles.
[0048] Among them, the crosslinking agent is hexamethylenetetramine; the number average molecular weight of polyacrylamide is 3 million; the particle size of fly ash is 120 mesh; the particle size of calcium oxide is 150 mesh; the number average molecular weight of chitosan is 500,000; the particle size of montmorillonite is 10 mesh; the length of brucite fiber is 5 mm. The rubber particles are selected from nitrile rubber particles, and the particle size of nitrile rubber particles is 120 mesh; the alkali in the alkali solution is selected from sodium hydroxide; and the weight proportion of the alkali in the alkali solution is 5 parts.
[0049] When preparing the material for solidifying metal ions in coal gangue, the materials are mixed evenly to obtain a mixture A; 200 parts of alkali solution and the mixture A are stored separately.
[0050] When the above material is used to solidify metal ions in coal gangue, the mixture A in the material is evenly mixed with the coal gangue to obtain a mixture B (the mass ratio of polyacrylamide to coal gangue is 1:4); the mixture B is spread into a 30 cm thick spreading layer; the heated alkali solution is added to the mixture B for reaction, wherein the alkali solution is added to the mixture B three times, and the amount of alkali solution each time is 1 / 3 of the volume of the alkali solution, the first alkali solution is added at a position 1 / 3 of the bottom layer of the spreading layer of the mixture B, and the second alkali solution is added at a position 2 / 3 of the bottom layer of the spreading layer of the mixture B, and the above rule is repeated until the alkali solution is added; the temperature of the first alkali solution addition is 80°C; the temperature of the alkali solution addition for the second and third times is 70 and 60°C; the time interval between each addition of the alkali solution is 20 minutes; after the above reaction, in-situ gelation is achieved, thereby solidifying the metal ions in the coal gangue and obtaining a coal gangue solidification layer.
[0051] Example 3
[0052] A material for solidifying metal ions in coal gangue, comprising the following raw materials in parts by weight:
[0053] 20 parts of polyacrylamide, 20 parts of fly ash, 8 parts of cross-linking agent, 15 parts of calcium oxide, 4 parts of chitosan, 5 parts of montmorillonite, 4 parts of brucite fiber and 3 parts of rubber particles.
[0054] Among them, the cross-linking agent is hexamethylenetetramine; the number average molecular weight of polyacrylamide is 5 million; the particle size of fly ash is 150 mesh; the particle size of calcium oxide is 100 mesh; the number average molecular weight of chitosan is 300,000; the particle size of montmorillonite is 20 mesh; and the length of brucite fiber is 3 mm.
[0055] The rubber particles are selected from nitrile rubber particles, and the particle size of the nitrile rubber particles is 80 meshes; the alkali in the alkali solution is selected from sodium hydroxide; and the weight proportion of the alkali in the alkali solution is 10 parts.
[0056] When preparing the material for solidifying metal ions in coal gangue, the raw materials except the alkali solution are mixed evenly to obtain a mixture A; 300 parts of the alkali solution and the mixture A are stored separately.
[0057] When the above material is used to solidify metal ions in coal gangue, the mixture A in the material is mixed with the coal gangue to obtain a mixture B (the mass ratio of polyacrylamide in the material to coal gangue is 1:6); the mixture B is spread into a 40 cm thick spreading layer; the heated alkali solution is added to the mixture B for reaction, wherein the alkali solution is added to the mixture B in 4 times, and the amount of alkali solution each time is 1 / 4 of the volume of the alkali solution, the first alkali solution is added at a position 1 / 4 of the bottom layer of the spreading layer of the mixture B, and the second alkali solution is added at a position 2 / 4 of the bottom layer of the spreading layer of the mixture B, and the above rule is repeated until the alkali solution is added; the temperature of the first alkali solution addition is 75°C; the temperatures of the alkali solution additions for the second to fourth times are 65, 55, and 45°C; the time interval between each addition of the alkali solution is 18 minutes; after the above reaction, in-situ gelation is achieved, thereby solidifying the metal ions in the coal gangue and obtaining a coal gangue solidification layer.
[0058] Example 4
[0059] A material for solidifying metal ions in coal gangue, comprising the following raw materials in parts by weight:
[0060] 40 parts of polyacrylamide, 10 parts of fly ash, 15 parts of cross-linking agent, 25 parts of calcium oxide, 1 part of chitosan, 10 parts of montmorillonite, 15 parts of brucite fiber, 1 part of rubber particles, and 400 parts of alkali solution.
[0061] Among them, the crosslinking agent is hexamethylenetetramine; the number average molecular weight of polyacrylamide is 3 million; the particle size of fly ash is 130 mesh; the particle size of calcium oxide is 140 mesh; the number average molecular weight of chitosan is 300,000-500,000; the particle size of montmorillonite is 10-20 mesh; the length of brucite fiber is 6 mm. The rubber particles are selected from nitrile rubber particles, and the particle size of nitrile rubber particles is 120 mesh; the alkali in the alkali solution is selected from sodium hydroxide; the weight proportion of the alkali in the alkali solution is 7 parts.
[0062] When preparing the material for solidifying metal ions in coal gangue, the raw materials except the alkali solution are mixed evenly to obtain a mixture A; the alkali solution and the mixture A are stored separately.
[0063] When the above material is used to solidify metal ions in coal gangue, the mixture A in the material is evenly mixed with the coal gangue to obtain a mixture B (the mass ratio of polyacrylamide in the material to coal gangue is 1:8); the mixture B is spread into a 40 cm thick spreading layer; the heated alkali solution is added to the mixture B for reaction, wherein the alkali solution is added to the mixture B in 4 times, and the amount of alkali solution each time is 1 / 4 of the volume of the alkali solution, the first alkali solution is added at a position 1 / 4 of the bottom layer of the spreading layer of the mixture B, and the second alkali solution is added at a position 2 / 4 of the bottom layer of the spreading layer of the mixture B, and the above rule is repeated until the alkali solution is added; the temperature of the first alkali solution addition is 80°C; the temperatures of the alkali solution additions for the second to fourth times are 70, 60, and 50°C; the time interval between each addition of the alkali solution is 15 minutes; after the above reaction, in-situ gelation is achieved, thereby solidifying the metal ions in the coal gangue and obtaining a coal gangue solidification layer.
[0064] Example 5
[0065] A material for solidifying metal ions in coal gangue, comprising the following raw materials in parts by weight:
[0066] 25 parts of polyacrylamide, 18 parts of fly ash, 8 parts of cross-linking agent, 16 parts of calcium oxide, 10 parts of chitosan, 6 parts of montmorillonite, 6 parts of brucite fiber, 5 parts of rubber particles and 250 parts of alkali solution.
[0067] Among them, the crosslinking agent is hexamethylenetetramine; the number average molecular weight of polyacrylamide is 5 million; the particle size of fly ash is 120 mesh; the particle size of calcium oxide is 140 mesh; the number average molecular weight of chitosan is 400,000; the particle size of montmorillonite is 15 mesh; the length of brucite fiber is 4 mm. The rubber particles are selected from nitrile rubber particles, and the particle size of nitrile rubber particles is 120 mesh; the alkali in the alkali solution is selected from potassium hydroxide; and the weight proportion of the alkali in the alkali solution is 8 parts.
[0068] When preparing the material for solidifying metal ions in coal gangue, the raw materials except the alkali solution are mixed evenly to obtain a mixture A; the alkali solution and the mixture A are stored separately.
[0069] When the above material is used to solidify metal ions in coal gangue, the mixture A in the material is evenly mixed with the coal gangue to obtain a mixture B (the mass ratio of polyacrylamide to coal gangue is 1:5); the mixture B is spread into a 30 cm thick spreading layer; the heated alkali solution is added to the mixture B for reaction, wherein the alkali solution is added to the mixture B three times, and the amount of alkali solution each time is 1 / 3 of the volume of the alkali solution, the first alkali solution is added at a position 1 / 3 of the bottom layer of the spreading layer of the mixture B, and the second alkali solution is added at a position 2 / 3 of the bottom layer of the spreading layer of the mixture B, and the above rule is repeated until the alkali solution is added; the temperature of the first alkali solution addition is 75°C; the temperature of the alkali solution addition for the second and third times is 65 and 55°C; the time interval between each addition of the alkali solution is 30 minutes; after the above reaction, in-situ gelation is achieved, thereby solidifying the metal ions in the coal gangue and obtaining a coal gangue solidification layer.
[0070] Comparative Example 1
[0071] The method is basically the same as that of Example 3, except that brucite fiber, chitosan, rubber particles and montmorillonite are not added to the material used for solidifying the metal ions in the coal gangue.
[0072] Comparative Example 2
[0073] The method is basically the same as that of Example 2, except that the material includes the following raw materials in parts by weight:
[0074] 50 parts of polyacrylamide, 5 parts of fly ash, 25 parts of cross-linking agent, 30 parts of calcium oxide, 15 parts of chitosan, 15 parts of montmorillonite, 20 parts of brucite fiber, 8 parts of rubber particles, and 400 parts of alkali solution used in combination.
[0075] Comparative Example 3
[0076] The method is basically the same as that of Example 2, except that the material includes the following raw materials in parts by weight:
[0077] 10 parts of polyacrylamide, 40 parts of fly ash, 1 part of cross-linking agent, 5 parts of calcium oxide, 0.5 parts of chitosan, 0.5 parts of montmorillonite, 2 parts of brucite fiber, 0.5 parts of rubber particles, and 100 parts of alkali solution used in combination.
[0078] Comparative Example 4
[0079] The method is basically the same as that of Example 1, except that 25-degree alkali solution is added to the mixture B at one time.
[0080] Comparative Example 5
[0081] The method is basically the same as that of Example 3, the only difference being that no calcium oxide is added to the material used to solidify the metal ions in the coal gangue.
[0082] Test method:
[0083] The solidified coal gangue in the above embodiment and comparative example and the same amount of coal gangue not solidified by any material were washed with the same amount of water, and the solidification rate of metal ions in the coal gangue in the above embodiment and comparative example was measured. The specific data are shown in the following Table 1:
[0084] The solidification rate is calculated from the leaching toxicity value of heavy metals before and after solidification:
[0085] Q=C0-C1 / C0
[0086] Wherein: Q is the solidification rate (%); C0 is the initial leaching concentration of heavy metals in the coal gangue without any solidification material (mg / L); C1 is the leaching concentration of heavy metals in the coal gangue after adding solidification material (mg / L).
[0087] Among them, LA-ICP-MS was used to analyze the Cr in the heavy metal release solution of coal gangue. 3+ , Cd 2+ , Cu 2+ , Pb 2+ The ion content was measured.
[0088] Table 1
[0089]
[0090] It can be seen that the material for solidifying metal ions in coal gangue prepared by the present invention through reasonable raw material ratio can effectively solidify the metal ions in coal gangue.
[0091] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present invention, but the present invention is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and essence of the present invention, and these modifications and improvements are also considered to be within the scope of protection of the present invention.
Claims
1. A material for solidifying metal ions in coal gangue, characterized in that: The material includes the following raw materials in parts by weight: 15-40 parts of polyacrylamide, 10-30 parts of fly ash, 5-15 parts of cross-linking agent, 10-25 parts of calcium oxide, 1-10 parts of chitosan, 1-10 parts of montmorillonite, 4-15 parts of brucite fiber, and 1-5 parts of rubber particles.
2. The material for solidifying metal ions in coal gangue according to claim 1, characterized in that The invention comprises the following raw materials in parts by weight: 20-30 parts of polyacrylamide, 10-20 parts of fly ash, 5-10 parts of cross-linking agent, 10-20 parts of calcium oxide, 2-6 parts of chitosan, 5-10 parts of montmorillonite, 5-8 parts of brucite fiber, and 1-3 parts of rubber particles.
3. The material for solidifying metal ions in coal gangue according to claim 1, characterized in that: The cross-linking agent includes one or more of N,N'-methylenebisacrylamide, phenolic resin, hexamethylenetetramine and formaldehyde.
4. The material for solidifying metal ions in coal gangue according to claim 3, characterized in that: The number average molecular weight of polyacrylamide is 3 million to 6 million; The particle size of fly ash is 120-150 mesh; The particle size of calcium oxide is 100-150 mesh.
5. The material for solidifying metal ions in coal gangue according to claim 3, characterized in that: The number average molecular weight of the chitosan is 300,000-500,000; The particle size of the montmorillonite is 10-20 mesh; The length of the brucite fiber is 3-6 mm.
6. The material for solidifying metal ions in coal gangue according to claim 1, characterized in that: The rubber particles are selected from nitrile rubber particles, and preferably the particle size of the nitrile rubber particles is 80-120 meshes; The alkali in the alkali solution is selected from sodium hydroxide and potassium hydroxide; The weight proportion of the alkali in the alkali solution is 5-10 parts.
7. A method for preparing a material for solidifying metal ions in coal gangue according to any one of claims 1 to 6, characterized in that: The following steps are involved: Mix the raw materials evenly.
8. An application of the material for solidifying metal ions in coal gangue as claimed in any one of claims 1 to 6, characterized in that: The material for solidifying metal ions in coal gangue is uniformly mixed with coal gangue to obtain mixture B; the mixture B is spread into a spreading layer with a thickness of 30-40 cm; the heated alkali solution is added to the mixture B to react to achieve in-situ gelation, thereby solidifying the metal ions in the coal gangue and obtaining a coal gangue solidification layer.
9. The use according to claim 8, characterized in that: The mass ratio of polyacrylamide to coal gangue in the material is 1:4-8; The heating temperature of the alkali solution is 30-80°C; The alkali solution is added to the mixture B in n times, and the amount of the alkali solution each time is 1 / n of the volume of the alkali solution. The first alkali solution is added at a position 1 / n away from the bottom layer of the spreading layer of the mixture B, and the second alkali solution is added at a position 2 / n away from the bottom layer of the spreading layer of the mixture B. The above rule is repeated until the alkali solution is added. The value range of n is 3-4.
10. The use according to claim 9, characterized in that: The temperature of the first alkali solution addition is 60-80°C; the temperature of the first alkali solution addition is recorded as T1, and the temperature of the nth alkali solution addition is T1-10(n-1); The time interval for adding alkali solution each time is 15-30 minutes.